Factors that Affect Perceived Value and Its Impact on the Value of Enrolling in Private Universities in Indonesia during the Pandemic - Hendra Achmadi; Ahmad Hidayat Sutawidjaya (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: This study was conducted to determine the factors that affect the perceived value and its impact on the value of enrolling in private universities in Indonesia during the pandemic.Methodology: The population in this study is high school students in grades 11 and 12 for the period from January to February 2022. The respondents are obtained using non-probabilistic with confidence sampling through google form questionnaire distribution, with 216 respondents to be analyzed using structural equation analysis (SEM) by Smart PLS application.Finding: The first finding is that negative emotion had an effect on the intention to enroll, the second finding was in research on the factors that influence online learning in university students. self-efficacy indicators play an important role in the successful online learning program, The third finding in this research is that e-service quality has more influence on functional value. The biggest influence on the Intention to Enroll is the epistemic value with the second being online learning, and the last one is the emotional value.Conclusion: In this pandemic period, universities must continue to improve epistemic values or values related to the quality of learning to be able to compete with other universities.